2022
DOI: 10.1097/mnm.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Current status of nuclear cardiology practice in Latin America and the Caribbean, in the era of multimodality cardiac imaging approach: 2022 update

Abstract: Cardiovascular diseases (CVDs) are the leading cause of mortality in Latin America and the Caribbean (LAC), with the risk in men being slightly higher than in women. The coronavirus disease 2019 (COVID-19) pandemic caused a significant reduction in the number of cardiac diagnostic procedures globally and in particular in LAC. Nuclear cardiology is available in the region, but there is variability in terms of existing technology, radiopharmaceuticals, and human resources. In the region, there are 2385 single ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…For example, only 5 surveys were collected from the Caribbean, potentially reflecting scarcity of cardiovascular imaging centers in the region, which could impact the generalizability of our findings. Indeed, a recent survey found that Cuba, the only Caribbean country included in the study, had fewer than five CT scanners per million inhabitants in 2022, and less than one MRI scanner, PET scanner, and cyclotron per million, [43] and as of 2020, Haiti, the most populous country in the region, had only four CT scanners serving over 11 million people, according to IAEA/Pan American Health Organization estimates, [44] and to the best of our knowledge none of these are used to perform coronary CTA. These statistics highlight the urgent need for international initiatives aimed at improving access to medical imaging in the Caribbean, such as those headed by the American College of Radiology Foundation and RAD-AID in Haiti [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, only 5 surveys were collected from the Caribbean, potentially reflecting scarcity of cardiovascular imaging centers in the region, which could impact the generalizability of our findings. Indeed, a recent survey found that Cuba, the only Caribbean country included in the study, had fewer than five CT scanners per million inhabitants in 2022, and less than one MRI scanner, PET scanner, and cyclotron per million, [43] and as of 2020, Haiti, the most populous country in the region, had only four CT scanners serving over 11 million people, according to IAEA/Pan American Health Organization estimates, [44] and to the best of our knowledge none of these are used to perform coronary CTA. These statistics highlight the urgent need for international initiatives aimed at improving access to medical imaging in the Caribbean, such as those headed by the American College of Radiology Foundation and RAD-AID in Haiti [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Countries with the highest number of scanners (CT, MRI, SPECT, and PET-CT) per million inhabitants are Argentina, Brazil, Chile, and Colombia, showing a substantial difference from the rest of the countries. 7 As a result, all of these factors contribute to disparities in patient care.…”
mentioning
confidence: 99%